2023
DOI: 10.3233/jad-230303
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Dementia Knowledge in German: Validation and Comparison of the Dementia Knowledge Assessment Scale, the Knowledge in Dementia Scale, and the Dementia Knowledge Assessment Tool 2

Abstract: Background: Assessing dementia knowledge is critical for developing and improving effective interventions. There are many different tools to assess dementia knowledge, but only one has been validated in German so far. Objective: To validate two tools for assessing dementia knowledge—the Dementia Knowledge Assessment Scale (DKAS-D) and the Knowledge in Dementia Scale (KIDE-D) for the German general population—and compare their psychometric properties with the Dementia Knowledge Assessment Tool 2 (DKAT2-D). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 69 publications
(139 reference statements)
4
14
2
Order By: Relevance
“…According to the original study [ 29 ] as well as the study of Melchior and Teichmann (2023) [ 36 ], no coherent structure was revealed for KIDE. Therefore, the structural validity of KIDE-G was not conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the original study [ 29 ] as well as the study of Melchior and Teichmann (2023) [ 36 ], no coherent structure was revealed for KIDE. Therefore, the structural validity of KIDE-G was not conducted.…”
Section: Resultsmentioning
confidence: 99%
“…The KIDE was translated into Greek by Gkioka (unpublished data, 2020) (KIDE-G), but since the alpha Cronbach was < 0.60, their data were not published. To date, the KIDE has been validated in the German population, showing poor reliability and a tendency to ceiling effect [ 36 ]. To our knowledge, it has not been validated in other languages.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed acceptable internal consistencies at baseline for all three scales. However, the German validation study in the general population showed good internal consistency with Cronbach’s alpha 0.83 –0.85 for the DAS-D [ 22 ], good internal consistency with Cronbach’s alpha of 0.87 for the DKAS-20-D [ 20 ], and excellent internal consistency with a Cronbach’s alpha of 0.91 for the CODE-D [ 22 ]. These differences between the original validation study and the present study may be due, among other things, to the fact that the scales in German were originally validated on the general population, whereas in the current study, they were transferred to the targeted group.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study review also demonstrated that the majority of studies with attitudinal outcomes reported positive improvements in attitudes after dementia training, with 27% of included studies showing no significant changes [ 40 ]. This can be explained, among other variables, by using inadequate scales, such as the KIDE scale in the German population, which failed to detect any improvements in knowledge about dementia after a dementia training [ 41 ] and failed to do so when comparing pre- and post-tests [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation